Prior entrepreneurial exposure and the emergence of entrepreneurial passion: The moderating role of learning orientation. (3rd March 2020) - Türk, Sarah; Zapkau, Florian B.; Schwens, Christian
ABSTRACT: Entrepreneurial passion is important for individuals to advance in the entrepreneurial process, but we lack a theoretical understanding of how passion develops. Drawing on social learning theory, the present study examines how prior entrepreneurial exposure (that is, entrepreneurial role model experience and direct entrepreneurial experience) affects entrepreneurial passion and how an individual's learning orientation moderates the relationship. To empirically validate our research model, we collected data from 928 students across several disciplines. Consistent with our theorizing, we find both types of prior entrepreneurial exposure to positively influence entrepreneurial passion. Further, medium to high levels of learning orientation strengthen these relationships.